Report of the Steering Committee on University Education open Learning System Technical and Management Education - Planning Commission (Planning Commission, Government of India, 1997)
The Report of the Steering Committee on University Education, Open Learning System, Technical and Management Education, prepared for the Ninth Five Year Plan (1997–2002) under the Chairmanship of Dr. D. Swaminadhan, provides a comprehensive framework for the development of higher education in India in the context of globalization, liberalization, and evolving economic policies. Recognizing the crucial role of higher, technical, and management education in human resource development and national growth, the report outlines strategies for consolidation, quality enhancement, access, equity, and relevance across educational sectors. Key recommendations include career development, research promotion, integration of women and marginalized groups, and expansion of open and distance learning through IGNOU and state open universities. Technical education is to be strengthened through mission-mode faculty development, industry-institute linkages, infrastructure modernization, flexible modular curricula, and accreditation systems. Management education emphasizes faculty creation, industry partnerships, curriculum restructuring, and private sector participation. The report highlights significant progress in the Eighth Plan, including establishment of new universities, expansion of distance education, and development of institutions like IITs, RECs, NERIST, and SLIET. Strategies for resource mobilization, use of technology for learning, promotion of open learning networks, national resource centers, and student mobility are emphasized. The overall objective is to create a robust, inclusive, and high-quality education system capable of producing skilled professionals, enhancing employability, fostering research and innovation, and meeting national and regional development needs.
Government of India Planning Commission December, 1997
Keywords: Higher Education; Open Learning System; Technical Education; Management Education; Distance Education; IGNOU; Skill Development; Faculty Development; Infrastructure Modernization; Equity and Access; Research and Innovation; Resource Mobilization